(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the socio-economic essence and significance of tax administration in tax policy. It also discusses the advanced experiences of foreign countries, their shortcomings and achievements in improving the tax system. The article primarily focuses on enhancing tax administration and includes analysis based on the opinions and views of economists in this field.